Aliran Realisme dalam Karya Sastra Arab - Hativa Sari (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This paper discusses one of school contained in aliterary work that is the school of realism. A school ofliterature usually appears preceded by another schooland is usually followed by a new school as a counterto the previous school. The purpose of this paper is todetermine the form of the school of realism and itsinfluence on literary works. The school of realism is aliterary school that seeks to describe an object as it is(realistic), not as it is. This school initially appeared inFrance and began to touch the Arab world, especiallyEgypt in the 20th century. There were many Egyptianwriters who were influenced and produced realistArabic literary works, one of which was Najib Mahfuz.